2019
DOI: 10.4103/ijo.ijo_1197_17
|View full text |Cite
|
Sign up to set email alerts
|

Effect of birth weight on retinopathy of prematurity in discordant twin pairs

Abstract: Purpose: Since twin pairs with discordance have equal gestational age (GA), discordant twins may constitute an appropriate group to investigate the specific effect that birth weight (BW) has on the development of retinopathy of prematurity (ROP). The present study aims to investigate the effect of BW on any and severe stages of ROP development in twin pairs. Methods: Fifty-two discordant twin pairs (104 preterms) born ≤32 gestational weeks, who were diagnosed with a min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Discordant twin pairs with lower birth weights are more prone to develop any stage of ROP. The advanced stage of ROP is seen more in higher-birth-weight twin pairs [ 23 ].…”
Section: Reviewmentioning
confidence: 99%
“…Discordant twin pairs with lower birth weights are more prone to develop any stage of ROP. The advanced stage of ROP is seen more in higher-birth-weight twin pairs [ 23 ].…”
Section: Reviewmentioning
confidence: 99%
“…Since twin pairs have equal gestational age, they investigated the specific effect that birth weight may have on the development of ROP and showed that birth weight plays an important role in any stage of ROP. [ 23 ] Insulin-like growth factor I (IGF-I) is an important somatic growth factor for fetal and neonates' growth and development that is correlated with birth weight. [ 24 , 25 ] Early levels of low IGF-I are associated with slower-than-expected weight gain and more severe ROP.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is still unknown which factor serves a larger contribution for the development of ROP as it is difficult to determine whether the prematurity precedes low birth weight or the other way around. (32) A worldwide database which collects data from over 1000 NICUs estimated ROP incidence of 33.2% of all infants weighing < 1500 g at birth in 2010. (4) Over the years, numerous studies have reported higher ROP incidence or more severe ROP developing in lighter birth weights.…”
Section: Discussionmentioning
confidence: 99%